Žibertova teorija zarote - Rahten, Andrej (ZRC SAZU, Založba ZRC, 2013)
On the anniversary of the Sarajevo assassination (28 June 1914), the booklet of Dr. Ivan Avguštin Žibert, Der Mord von Sarajevo und Tiszas Schuld an dem Weltkriege, provides a good motivation for reflection on the causes of this fateful event. Appearing as a facsimile is its third edition, which was self-published in 1919. Although comprising not more than forty-seven pages, it touches on many events and personages connected to the heir apparent Franz Ferdinand. In the introduction to the facsimile of Žibert's booklet, Prof. Andrej Rahten, PhD, wrote the study "Ozadja in okoliščine nastanka Žibertove teorije zarote" ["The backgrounds and circumstances of Žibert's conspiracy theory"], offering a clear view of the problem concerning the events that unfolded in Sarajevo. Rahten provides a detailed insight into the life of the heir apparent Franz Ferdinand and his morganatic wife Sophie von Hohenberg on the eve of the First World War.